SARS‐CoV‐2, HIV, and HPV: Convergent evolution of selective regulation of cGAS–STING signaling. Issue 1 (26th October 2022) - Shen, Si; Rui, Yajuan; Wang, Yanpu; Su, Jiaming; Yu, Xiao‐Fang
Abstract: Recognizing aberrant cytoplasmic double‐stranded DNA and stimulating innate immunity is essential for the host's defense against viruses and tumors. Cyclic GMP–AMP (cGAMP) synthase (cGAS) is a cytosolic DNA sensor that synthesizes the second messenger 2′3′‐cGAMP and subsequently activates stimulator of interferon genes (STING)‐mediated activation of TANK‐binding kinase 1 (TBK1)/interferon regulatory factor 3 (IRF3) and the production of type I interferon (IFN‐I). Both the cGAS–STING‐mediated IFN‐I antiviral defense and the countermeasures developed by diverse viruses have been extensively studied. However, recent studies have revealed a convergent evolutionary feature of severe acute respiratory syndrome coronavirus 2 and human immunodeficiency virus (HIV) viral proteins in terms of the selective regulation of cGAS–STING‐mediated nuclear factor‐κB (NF‐κB) signaling without any effect on cGAS–STING‐mediated TBK1/IRF3 activation and IFN production. The potential beneficial effect of this cGAS–STING‐mediated, NF‐κB‐dependent antiviral effect, and the possible detrimental effect of IFN‐I in the pathogenesis of coronavirus disease 2019 and HIV infection deserve more attention and future investigation.